Hayman conjecture for p-adic meromorphic functions in several variables - An, Vu Hoai; Le Thu, Thi Hoai (P-adic numbers, ultrametric analysis, and applications, 2012)
In this paper we prove a generalized version of the Hayman Conjecture for p -adic meromorphic functions in several variables.